2013
DOI: 10.1186/1556-276x-8-119
|View full text |Cite
|
Sign up to set email alerts
|

DNA nanotechnology: a future perspective

Abstract: In addition to its genetic function, DNA is one of the most distinct and smart self-assembling nanomaterials. DNA nanotechnology exploits the predictable self-assembly of DNA oligonucleotides to design and assemble innovative and highly discrete nanostructures. Highly ordered DNA motifs are capable of providing an ultra-fine framework for the next generation of nanofabrications. The majority of these applications are based upon the complementarity of DNA base pairing: adenine with thymine, and guanine with cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
34
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 93 publications
0
34
0
Order By: Relevance
“…Deoxyribonucleic acids (DNAs) are one of the major building blocks of biological systems. Recently, researchers have been exploiting DNA self-assembly for constructing nanostructures as well as programming molecular devices [1][2][3][4][5][6][7][8][9][10][11][12][13]. Yurke et al first observed the phenomenon of DNA strand displacement in their nanomachine [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deoxyribonucleic acids (DNAs) are one of the major building blocks of biological systems. Recently, researchers have been exploiting DNA self-assembly for constructing nanostructures as well as programming molecular devices [1][2][3][4][5][6][7][8][9][10][11][12][13]. Yurke et al first observed the phenomenon of DNA strand displacement in their nanomachine [14].…”
Section: Introductionmentioning
confidence: 99%
“…Lanes 2, 3, and 4 contain a mixture of two hairpins (H 6-7 ), three hairpins (H 6-8 ), and four hairpins (H 6-9 ), respectively without the initiator: products of high molecular weight are slightly visible, indicating evidence of some leak. Lanes 5, 6, 7 contain a mixture of H 6-7 , H[6][7][8] , and H 6-9 , respectively with the initiator: products of high molecular weight are visible, indicating strong evidence of linear cascade reactions. A mismatch of hairpin concentrations is also visible in lines 7 and 8.…”
mentioning
confidence: 99%
“…To achieve these detection methods, plant pathologists are working with nanotechnologists to develop quick and better detection systems (Sharon et al, 2010). DNA has also become a preferred material for nanotechnologists because of its unique properties of structural stability, programmability of sequences, and predictable selfassembly (Zahid et al, 2013). Magnetic nanoparticles (MNPs) consisting of magnetite (Fe3O4) are promising as nanodiagnostic tools in plant pathology (Alghuthaymi et al, 2016;Khiyami et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This paper seeks to identify and address the many experimental problems to which the DNA double helix model seems to offer no solution such as the inevitable topological complexity of the DNA octahedron (Zahid et al, 2013). Thus the body of DNA studies in nanotechnology can be strengthened and fresh approaches to potential developments in DNA nanotechnology can be identified.…”
Section: Introductionmentioning
confidence: 99%
“…Though the DNA cube, and DNA octahedron (Zahid et al, 2013) for example, are well known and have been drawn in detail, the evident complexity of such molecules, and other, comparable constructs using the double helix, seems to constitute a formidable obstacle to attempts to further develop such concepts and to widen the use of such DNA constructs in medicine, computing and in nanorobotics.…”
Section: Introductionmentioning
confidence: 99%